Poster No. 133 Local TGF-beta sequestration by fibrillin-1 regulates vascular wall homeostasis in the thoracic aorta. (21st October 2022) - de Backer, Julie; de Leeuw, Violette; Van Impe, Mathias; Vanhomwegen, Marine; Logghe, Gerlinde; Oblinado, Margie; Stampanoni, Marco; Segers, Patrick; Mosquera, Laura Muino; Sakai, Lynn; Sips, Patrick
Abstract: Introduction: Marfan syndrome (MFS) is caused by a defect in fibrillin-1, which binds TGF-beta via interaction with latent TGF-beta binding proteins (LTBPs). The role of TGF-beta in MFS is controversial. Objectives: use dedicated mouse models for MFS, with defects interfering with TGF-beta binding and function, to gain insights into the role of TGF-beta signaling in aneurysm formation and dissection. Material & methods: Mice lacking the binding site for LTBPs ( Fbn1 H1Δ/+ and Fbn1 H1Δ/H1Δ ), mice with a truncated fibrillin-1 ( Fbn1 GT-8/+ ), and mice with a combination ( Fbn1 GT-8/H1Δ ) were subjected to cardiac ultrasound and ex vivo synchrotron X-ray imaging. Results: Only Fbn1 GT-8/H1Δ mice showed increased mortality (aortic rupture) starting at 4–5 months, whereas all other mice had a normal life span. Aortic root dilatation occurred both in Fbn1 GT-8/+ and Fbn1 GT-8/H1Δ mice at 6 months, but not in Fbn1 H1D/+ or Fbn1 H1Δ/H1Δ mice. Significant elastin fragmentation was observed in the thoracic aortic wall of Fbn1 GT-8/+ mice, and to a larger extent in Fbn1 GT-8/H1Δ mice. Surprisingly, localized elastin fragmentation was also found in the ascending aorta of Fbn1 H1Δ/+ and Fbn1 H1Δ/H1Δ mice, despite a lack of aortic aneurysm formation. Moreover, Fbn1 H1Δ/H1Δ mice displayed more severe aortic wall damage. Conclusion: Our data suggest that loss of LTBP binding to fibrillin-1 leads to the development of localized aortic microdissections in the absence of aortic aneurysm, and exacerbates the aortic wall morphology abnormalities in mice with truncated fibrillin-1. We therefore hypothesize that local TGF-beta sequestration is required to maintain aortic homeostasis.